IMPACTS OF DEREGULATED AND REGULATED ELECTRIC VEHICLE CHARGING IN A DISTRIBUTION NETWORK (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The transportation sector contributes highly to environmental issues. With awareness of such issues, electric vehicles (EVs) have emerged as the solution in the transport sector. But at the same time, their higher penetration may cause grid issues since they are considered the additional load to the current grid. This paper presents the impact of deregulated and regulated electric vehicle (EV) charging scenarios on a real medium voltage (MV) grid in Gračanica. The grid modeling and quasi-dynamic simulation were done in DIgSILENT PowerFactory software. The analysis was done with data from Public Enterprise Elektroprivreda of Bosnia and Herzegovina. The regulation of charging was made by valley filling. This approach ensured the 100% penetration of EVs for the analyzed grid. Regulated EV charging scenarios impact the active power of the complete grid by shaving daily peaks compared to deregulated charging. All EV charging scenarios did not violate voltage limits defined by EN 50160.
Keywords: Electric vehicle; Medium-voltage network; Deregulated charging; Regulated charging; Valley filling; Quasi-dynamic simulation